Ecosystem with creativity, research and innovation based on transversal competences facing the professional demands of the 21st century - Romero Carrión, Violeta L. (2020)
The objective of the research was to determine if the Ecosystem with creativity, research and innovation, based on transversal competences, responds to the professional demands of the 21st century. For the study, the questionnaire of transversal competences, of the Tuning Project, was applied, aimed at 30 university students, in which case the achievement in their training was investigated, while, in the case of the 30 employers, it was to know the importance of assigned to the competencies that new professionals should possess. After testing the normality of the data distribution, the Student's t hypothesis test statistic was applied for independent samples, obtaining a highly significant value, with respect to the fact that the competences included in the Ecosystem with creativity, research and innovation, They are different, between what has been achieved by students and what is demanded of new professionals by the employers of 21st century organizations. It is recommended to reduce the gap between transversal skills, achieved by university students and those required by employers, through frequent updating of the study curriculum according to the demands of the labor market.